2012
DOI: 10.1126/science.1222218
|View full text |Cite
|
Sign up to set email alerts
|

Uniform ripening Encodes a Golden 2-like Transcription Factor Regulating Tomato Fruit Chloroplast Development

Abstract: Modern tomato (Solanum lycopersicum) varieties are bred for uniform ripening (u) light green fruit phenotypes to facilitate harvests of evenly ripened fruit. U encodes a Golden 2-like (GLK) transcription factor, SlGLK2, which determines chlorophyll accumulation and distribution in developing fruit. In tomato, two GLKs--SlGLK1 and SlGLK2--are expressed in leaves, but only SlGLK2 is expressed in fruit. Expressing GLKs increased the chlorophyll content of fruit, whereas SlGLK2 suppression recapitulated the u muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
381
1
8

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 396 publications
(422 citation statements)
references
References 47 publications
14
381
1
8
Order By: Relevance
“…It was recently reported that the u mutation of the SlGLK2 gene is responsible for the light-green phenotype in cultivated tomato varieties (Powell et al, 2012), and that overexpression of SlGLK2 and its paralog SlGLK1 leads to dark-green fruit similar to those described in down-regulated SlARF4. However, even though the expression of SlGLK2 was found to be significantly enhanced in SlARF4 down-regulated lines, it cannot account for the dark-green phenotype of the transgenic fruit, since the cv Micro-Tom variety bears the inactive u allele of SlGLK2.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…It was recently reported that the u mutation of the SlGLK2 gene is responsible for the light-green phenotype in cultivated tomato varieties (Powell et al, 2012), and that overexpression of SlGLK2 and its paralog SlGLK1 leads to dark-green fruit similar to those described in down-regulated SlARF4. However, even though the expression of SlGLK2 was found to be significantly enhanced in SlARF4 down-regulated lines, it cannot account for the dark-green phenotype of the transgenic fruit, since the cv Micro-Tom variety bears the inactive u allele of SlGLK2.…”
Section: Discussionmentioning
confidence: 86%
“…Considering that the chlorophyll and starch phenotypes of SlARF4 ASLs are reminiscent of those described in tomato GOLDEN2-LIKE (SlGLK) overexpressing lines (Powell et al, 2012), we addressed the putative link between the expression of this MYB-type transcription factor and the phenotypes displayed by the SlARF4 transgenic lines. Two GLK genes (SlGLK1 and SlGLK2) are present in the tomato genome, and it was reported that in most domesticated genotypes the SlGLK2 gene bears the uniform ripening (u) mutation that results in light-green fruit phenotype.…”
Section: Expression Analysis Of Slglk Genesmentioning
confidence: 99%
“…4). In contrast, CNR 50 , Uniform (Golden-like 2) 51 and HB-1 (ref. 52) showed distinct expression patterns in hot pepper and tomato (Fig.…”
Section: Comparative Fruit Ripeningmentioning
confidence: 99%
“…The important role of the GLKs is 173 reinforced by the pale glk1glk2 double mutant with partially developed chloroplasts and a, albeit 174 weak, gun phenotype (Fitter et al, 2002;Waters et al, 2009). Although genetic analyses 175 indicated that GLK1 and GLK2 are redundant, recent work has revealed specificity that is 176 regulated at transcriptional and post-transcriptional levels (Powell et al, 2012;Kobayashi et al, 177 2013;Wang et al, 2013;Martín et al, 2016;Tokumaru et al, 2017). 178…”
Section: ) 162 163mentioning
confidence: 99%
“…The GLK transcription factors have been shown to be implicated in fruit development, for 404 example through the pale siliques of the Arabidopsis glk2 mutant or the identification of GLK2 405 as the locus affected in the uniform ripening (u) mutation that results in uniformly green 406 tomatoes (Waters et al, 2008;Powell et al, 2012;Nguyen et al, 2014). Similarly, a correlation 407 was reported between CaGLK2 and variation in chlorophyll content and colour in pepper fruit 408 (Brand et al, 2014).…”
mentioning
confidence: 99%